1983
DOI: 10.1103/physrevc.28.1527
|View full text |Cite
|
Sign up to set email alerts
|

Pre-equilibrium emission of light composite particles in the framework of the exciton model

Abstract: The exciton model for the pre-equilibrium emission of light composite particles proposed and applied to the (p,n) reaction of Iwamoto-Harada is further investigated for the energy spectra of the (p,d), (p,t), and (p, 'He) reactions with incident energy of several tens of MeV's. Calculated results could reproduce an overall feature of those spectra. The dominance of the pickup-type contribution which occurs in the course of the equilibration process was found to be common for all composite particles. The degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 8 publications
1
42
0
Order By: Relevance
“…GNASH uses phenomenological expressions by Kalbach [55,64] while EMPIRE employs the IwamotoHarada model [65] parameterized and improved in Refs. [66][67][68]. The latter model contains two essential features that increase production of composite particles during the equilibration stage:…”
Section: F Coupling Between Msc and Msd In Empirementioning
confidence: 99%
“…GNASH uses phenomenological expressions by Kalbach [55,64] while EMPIRE employs the IwamotoHarada model [65] parameterized and improved in Refs. [66][67][68]. The latter model contains two essential features that increase production of composite particles during the equilibration stage:…”
Section: F Coupling Between Msc and Msd In Empirementioning
confidence: 99%
“…It has recently been demonstrated that the preequilibrium LCP emission can be described reasonably well by implementation of a surface a Presenting author, e-mail: watanabe@aees.kyushu-u.ac.jp coalescence mechanism in the INC model for nucleon-induced reactions at several hundreds of MeV to 2.5 GeV [11,12]. In the past, a similar coalescence idea was taken into account in the preequilibrium exciton model, and successfully applied to light-ion production in proton-induced reactions at incident energies below 100 MeV [13][14][15]. In the present work, we also implement such a phenomenological surface coalescence model into the QMD simulation [16].…”
Section: Introductionmentioning
confidence: 98%
“…Some modifications [16] have been made in the QMD calculation on the basis of the phenomenological prescriptions incorporated in the INC model by Letourneau et al [11] and Boudard et al [12], and the coalescence exciton model by Iwamoto et al [13,14] and Bisplinghoff [15].…”
Section: Phenomenological Surface Coalescence Modelmentioning
confidence: 99%
“…The number of neutrons and protons for initial exciton state was calculated using realistic nucleon-nucleon interaction cross sections in nucleus [9]. The exciton coalescence pick-up model [11,12] and the knock-out model [13] were used for the description of the pre-equilibrium complex particle emission.…”
Section: Theoretical Predictionsmentioning
confidence: 99%